Revisiting investments and subsidies to accelerate agricultural income and alleviate rural poverty in India - Bathla, Seema; Joshi, Pramod Kumar; Kumar, Anjani (International Food Policy Research Institute, 2017)
This study tests the hypothesis that differences in public spending explain interstate variations in land productivity, income, and rural poverty. More important, it aims to comprehend the contribution of key social and economic public investments along with private (farm household) investment toward agricultural income and inclusive growth. We address the following four key issues. First, what has been the magnitude of public expenditure and private investment on key services in rural India from 1981 to 2013, and how do states compare? Second, has the composition of public spending within the social and economic categories/heads changed across the states? If yes, has it affected the capital intensity in agriculture and irrigation? Third, what is the impact of key investments and input subsidies on farm productivity, income, and poverty alleviation, and which investment yields higher marginal returns? Last, is there any nexus between efficiency and welfare objectives due to public expenditure at the disaggregate level, and how can it be addressed?